Modeling for preliminary analysis of core wall / Noorul Azmah Abdul Aziz - Abdul Aziz, Noorul Azmah (Faculty of Civil Engineering, 2006)
Reinforced concrete core wall is commonly used in high rise building that can provide a major part of the bending and torsional resistance in the building structure. Therefore, the engineer must be a responsible to make a safe design for the human comfort as well. The study on torsional behaviour of core wall is the most important thing while designing the high rise building structure. In this project, there are three models of core wall to be analyzed; core wall with opening, core wall partially closed by shallow beams and core wall partially closed by deep beams. The minimum and maximum principle stresses are obtained from the linear finite element analysis to determine the ultimate load that can be sustained for each model. The loads are assigned to the model until the model experienced crack and crush. The behaviour of core wall and the connecting beams subjected to torsional loading also had been analyzed using LUSAS package version 13.5. The model is not considered with any constraint effect from slab, beam and column. The beams contributed to the stiffness in torsion. The ultimate load for core wall partially closed by shallow beams is greater than core wall partially closed by deep beams.